On the Philosophical Life: A Refutation of Cultural Theory's Impossibility Theorem - NOWACKI, Mark (Institutional Knowledge at Singapore Management University, 2004)
Cultural Theory (CT) is breathtaking in its comprehensiveness and in its simplicity. With regard to CT’s comprehensiveness, it is entirely characteristic that when the three authors of Cultural Theory get around to asking themselves “What does cultural theory leave out?”, their answer turns out to be a hearty “Not much!” (Thompson, Ellis and Wildavsky 1990: 269-73) In a single work, Michael Thompson manages to credit CT with shedding light on everything from environmental policies and Kondratiev waves, to Everest expeditions, the literary preferences of Benjamin Disraeli, and Aristotle’s four causes. (Thompson 1996)